Bartholomew and the oobleck - Seuss, Dr. (New York : Random House, 1976)
Bartholomew Cubbins saves the kingdom when the oobleck comes down green and sticky from the sky.
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Booklist, April 2007.
Child Study Children's Book Committee, November 2009.
Elem. School Library Collection, June 2000.
Keywords: Humorous stories; Humorous fiction